Acalabrutinib in management of chronic lymphocytic leukemia: An Indian perspective. Issue 3 (28th May 2021) - Sood, Nitin; Varghese, Abraham; Chakrabarty, Joydeep; Chezhian, Subhash; Sopory, Pranav
Abstract: The treatment landscape of chronic lymphocytic leukemia (CLL) has witnessed immense changes in the past decade. Several newer target therapies and their combinations with anti‐CD 20 therapies have got approval for management of CLL in the treatment‐naïve and relapsed/refractory setting. Also, the availability of newer diagnostic techniques has helped differentiate the disease into high‐ and low‐risk CLL which acts not just as a prognostic marker but also helps decide the best drug management that can be administered to the patients. Targeted therapy has largely overtaken chemoimmunotherapy in the management of CLL, except for a small subset of the population (young and fit with IGHV mutation). However, with targeted therapy, there is also an issue of previously uncommon treatment‐emergent adverse events, the duration of therapy, and financial toxicity. The aim of this review article is to gather results from all landmark CLL trials and discuss the feasibility of incorporating Acalabrutinib in the CLL landscape from an Indian perspective.